PERLINDUNGAN PENGGUNA KE ATAS SKIM PELANCONGAN DI MALAYSIA - Samudin, Siti Aisyah; Zakaria, Zalina (Journal of Shariah Law Research, 2017)
Tourist Scheme is a holiday plan and travel provided by any travel agencies registered under the Ministry of Tourism and Ministry of Finance in Malaysia. Usually, it offers vacation packages include low cost of fee, tour guide service, low-cost accommodation and other services as an attraction to their customers or users. This study aimed to analyze the setup of the extent to which the relevant laws tourism scheme to protect the rights of consumers in Malaysia. The main method in carrying out this study is the analysis of documents and interview conducted with Mr. Mohammad Nordin Ab. Rauf as a Vice President of Tribunal for Consumer Claims Malaysia (TTPM). The findings show that existing law is adequate and able to protect consumers from fraudulent schemes tourism, as the legal provisions are there to prosecute the parties who breach the contract thus protecting the consumers.